MARITAL STATUS AND SUBJECTIVE WELL-BEING: DOES EDUCATION LEVEL TAKE INTO ACCOUNT? - Ndayambaje, Edmond; Pierewan, Adi Cilik; Nizeyumukiza, Emmanuel; Nkundimana, Balthazar; Ayriza, Yulia (Jurnal Cakrawala Pendidikan, 2020)
Following western trends besides several Asian countries, Indonesian families are experiencing an increase numbers of single men and women which seems to ignore traditional standards ages of getting married for both gentlemen and ladies. Indonesian youth in this category are subjected to social pressure to marry, and this affect their subjective well-being. Using data from Indonesian Family Life Survey (IFLS) 2014; 5th wave with 29,160 participants (15,581 women and 13,579 men) from 15,160 households and 297 Districts, This study was aimed at studying how marital status and subjective well-being are related in Indonesia, and how education take into account. Linear regression was performed to calculate the estimation correlation. After controlling confounding variables, the results show that married people are happier than singles, divorced, and widowers. In educational field, the research findings revealed that highly educated people are happier and satisfied than those who are less educated. Based on the results of this study, governments, policymakers, and their stakeholders need to encourage people to be engaged in education so that they rise their happiness. Further research orientations and recommendations were discussed for future researchers and policymakers to improve people's well-being.